PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN LABU KUNING UNTUK MENINGKATKAN EKONOMI KREATIF DI DESA PENGADANGAN, KECAMATAN PRINGGASELA, LOMBOK TIMUR - Sanad, Hanif; Jurnal Wicara; Al-Huda, M. Karsa Gaesa; M, Intan; Bakary, Najwa; Widiastuti, Ni Made; Sari, Defi; Aulia, Millah; Angelina, Novita; Putri, Dita; Ramadhani, Muhammad; Al-Huda9, M. Karsa Gaesa (Universitas Mataram, 2025)
The Community Service Program (KKN) of Universitas Mataram in Pengadangan Village, Pringgasela District, East Lombok, focused on community empowerment through the optimization of local potential, namely pumpkin (Cucurbita moschata). This commodity has generally been used only for household consumption without product diversification. This study employed surveys, observations, interviews, and documentation to design work programs, including agricultural product utilization workshops, pumpkin chips production training, and product packaging design socialization. The results indicate an improvement in community knowledge and skills, particularly among PKK women and village cadres, in processing pumpkins into value-added products with various flavors. The resulting product, “Keripik LabuKu,” served as a tangible output of the program, complemented by attractive and informative packaging design. This program contributed to enhancing creativity, creating new business opportunities, and strengthening the economic independence of Pengadangan Village.